The biopolitics of private conservation: jeopardizing labor and rhino to optimize capital? - Lerato Thakholi (Journal of Political Ecology, 2021)
The conservation of biodiversity has increasingly been analyzed as biopolitical. That is, conservation initiatives such as breeding programs and protected areas seek to optimize some nonhuman life forms while exposing others to harm or degradation. Biopolitical conservation studies have looked at the implications of how human and non-human lives have been valued differently. Wildlife has received more attention than the lives of conservation laborers in studies of private conservation. The article builds on Foucault's conceptualization of biopolitics to dissect the responses of the eco-tourism and wildlife breeding industries to rhino poaching in the Lowveld, South Africa. There are two central arguments. First, their responses hinge on creating new, and re-instating old, avenues of capital accumulation that ironically prioritize the optimization of the wildlife economy over the lives of rhino. Second, I show that private conservation disproportionately exposes black laborers to harm while attempting to protect rhino from poachers, a function of how conservation labor has been governed since the onset of poaching in 2008. I conclude that private conservationists in South Africa make value judgments to construct a hierarchy of life with whiteness at its apex, rhinos following closely behind, with laborers, and finally poachers at the bottom.